Tradisi Mipit Pare sebagai Upaya Pelestarian Nilai Budaya Lokal dalam Kehidupan Masyarakat Dusun Ciampel - Saadah Saadah; Fitri Silvia Sofyan; Yudi Firmansyah (KOLONI, 2026)
This research aims to examine the Mipit Pare tradition as an effort to preserve local cultural values in the lives of the people of Ciampel Hamlet. Mipit Pare is a tradition that is carried out before the implementation of the rice harvest as a form of gratitude for the agricultural products obtained and as a form of respect for cultural values that have been inherited from generation to generation. This research uses a qualitative approach with a field descriptive method. Data was obtained through participatory observation and in-depth interviews with traditional leaders, farmers, the younger generation, communities, and religious leaders in Ciampel Hamlet in May 2026. The results of the study show that the Mipit Pare tradition not only functions as a ceremonial activity before harvest, but also contains various cultural values that are important for peoples lives. These values include gratitude, mutual cooperation, togetherness, respect for nature, and the preservation of the cultural identity of the local community. This tradition also acts as a means of inheriting social values and norms to the younger generation so that the sustainability of local culture can be maintained in the midst of the development of the times and modernization currents. In addition, the implementation of the Mipit Pare tradition is able to strengthen social solidarity and strengthen relationships between community members through joint involvement in various series of traditional activities. Thus, the Mipit Pare tradition has a strategic role in maintaining the sustainability of local culture while strengthening the social cohesion of the people of Ciampel Hamlet. Therefore, efforts to preserve this tradition need to continue to be carried out as part of strengthening cultural identity and local cultural heritage.